Qaul as a Paradigm of Message Theory: Toward a Philosophy of Islamic Communication Science - Taqiyuddin, Muhammad; Hadi Ihsan, Nur; Wahyudi, Muhammad; Nasution, Alhafidh; Fahmy Zarkasyi, Hamid (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2025)
This article examines the concept of Qaul as a foundational paradigm for message theory within Islamic communication studies. While dominant communication theories commonly conceptualize messages as neutral units of information exchange, the Islamic intellectual tradition understands speech as an ethically accountable act with social and moral consequences. This study aims to elaborate on the multidimensional character of Qaul within Islamic epistemology and to explore its relevance for contemporary communication discourse. Using a conceptual qualitative approach based on library research, the study analyzes classical Islamic sources together with contemporary literature in communication studies. The analysis demonstrates that Qaul cannot be reduced to a merely linguistic act or a vehicle for information transmission; rather, it represents a normative communicative construct that shapes belief formation, ethical orientation, and social cohesion. The findings indicate that Qaul operates simultaneously across cognitive, moral, and relational dimensions, thereby situating communication within a framework of responsibility and accountability. Furthermore, the article highlights the relevance of the Qaul paradigm for contemporary communication practices, particularly within digital environments characterized by information abundance, fragmentation, and ethical ambiguity. By proposing an integrative theoretical framework, this study positions Qaul as a core concept that can enrich existing message theories and contribute to the development of a distinctive philosophy of Islamic communication grounded in Islamic epistemology.